Characterization of low adsorption filter membranes for electrophoresis and electrokinetic sample manipulations in microfluidic paper-based analytical devices. Issue 29 (10th July 2018) - Casto, Laura D.; Schuster, Jennifer A.; Neice, Claire D.; Baker, Christopher A.
Abstract : Low adsorption filter membrane materials facilitate effective zonal electrophoresis and electrokinetic gating in microfluidic paper-based analytical devices (μPADs). Abstract : The emergence of microfluidic paper-based analytical devices (μPADs) has renewed interest in paper as a substrate for chemical separations and analysis. The availability of engineered filter membrane materials effectively broadens the definition of "paper" as a substrate material, and presents the opportunity to utilize their engineered properties in chemical analyses. Here we evaluate a selection of low adsorption filter membrane materials for their efficacy in achieving zonal electrophoretic separations of amino acids within μPADs. Cellulose acetate (Whatman OE66), cellulose ester (MF-Millipore), and polyvinylidene fluoride (Durapore PVDF) substrates were evaluated for their performance in electrokinetic μPADs, including establishing microfabrication parameters, characterizing Joule heating, and establishing fluorescence detection limits. Heating-limited electric fields in the range of 230–350 V cm −1 were achieved, and fluorescence limits of detection of ca. 3 nM were observed in both green (fluorescein) and red (Nile blue) fluorescence channels for OE66 substrates. Electrophoretic separations of a three amino acid mixture were demonstrated in PVDF and OE66 μPADs, while relatively high rates of electroosmotic flow in MF-Millipore substrates enabled electrokinetic flow gating in this material. These studies demonstrate the efficacy of zonal electrophoresis in μPADs made from low adsorption substrates, and highlight design considerations for the development of similar μPAD systems.